Comparative assessment of residents' satisfaction with older and younger condominiums: case studies from Kuala Lumpur, Malaysia (UP 046) - Mohit, Mohammad Abdul; Ogundele, Ashim Oladimeji (2011)
During the last two decades, the growth of condos in Kuala Lumpur as a high density housing is a respose to the growing demand for housing in the city. So far housing research in Malaysia is focussed on public or private low-cost with little attention paid to the growing condo sector. Therefore, a research need arises due to limited studies on the subject and further that due to more than one reason. Malaysian middle class city dwellers prefer to live in condos than their preferred terrace housing. Against the above backdrop, this paper provides a comparative assessment of residents' satisfaction with older (>10 years) and younger (<10 years) condo dwellers within the Kuala Lumpur metropolis. Three components of satisfaction - dwelling unit variables, dwelling unit support services, neighbourhood and management, have been studied. Two hundred respondents participated in the survey exercise with 100 residing in older condos and another 100 living in younger condos. Findings from the study indicate that the residents of older condos are not satisfied with the dwelling unit support services and management and over 40% of the residents are also planning to relocate due to current housing situation. On the contrary, the younger condo residents rated a relatively high level of satisfaction with the dwelling unit support services and they are moderately satisfied with condo management. Further, the older condo residents showed a more significant and positive relationship between the overall housing satisfaction and the tested variables as compared to the younger condo residents due to the age differences between the two condo types. Finally, the paper comes up with three basic issues where immediate attentions are required to improve condo management enhance condo residents' satisfaction.